Currency, credit and commerce : early growth in Southeast Asia - Drake, P. J. (Peter Joseph) (Burlington, VT : Ashgate, 2004)
This book demonstrates the importance of acceptable, convertible money in underpinning and promoting economic development and of a sustained surplus on the balance of international payments for increasing the supply of money. it also examines securities markets in the later stage of development when funds for investment depend on collective rather than individual sources
Includes bibliographical references and index.
nmn 10/05/13
Loans
Keywords: Monetary policy -- Southeast Asia; Finance -- Southeast Asia; Southeast Asia -- Economic conditions; International economic relations